Direct percutaneous transaxillary implantation of a novel self‐expandable transcatheter heart valve for aortic stenosis. Issue 7 (15th March 2017) - Deuschl, Florian; Schofer, Niklas; Seiffert, Moritz; Hakmi, Samer; Mizote, Isamu; Schaefer, Andreas; Schirmer, Johannes; Reichenspurner, Hermann; Blankenberg, Stefan; Conradi, Lenard; Schäfer, Ulrich
Abstract : Objectives: The aim of this study was to evaluate safety, feasibility, and efficacy of transaxillary TAVI using a novel self‐expandable transcatheter heart valve (THV) via a direct percutaneous technique. Methods: The analysis comprises 12 consecutive patients with severe aortic stenosis treated with the ACURATE Neo™ THV (Symetis) by direct percutaneous transaxillary access. Results: Patients presented with a mean age of 79.9 ± 6.2 years and high calculated surgical risk (logEuroSCORE I: 19.55 ± 15.00%; STS PROM score: 5.42 ± 3.25%). Transaxillary TAVI was performed in 11/12 via the left and in 1/12 via the right‐sided axillary artery. Device success was achieved in all patients (12/12). Mortality rate at 30 days was 0% (0/12). No major and one minor access site complication (1/12) occurred. No major or life‐threatening access site‐related bleeding resulted. None of the patients suffered from postprocedural stroke/transient ischemic attack. There was no need for a permanent pacemaker. Mean effective orifice area post implantation was 2.1 ± 0.29 cm 2 and mean aortic gradient 6.2 ± 1.5 mm Hg. In none of the patients, greater than moderate aortic regurgitation or paravalvular leakage was detected at discharge (0/12). Conclusions: Our study suggests that the implantation of the second‐generation self‐expandable ACURATE Neo™ via a transaxillary access is technically feasible and safe and yields excellent short‐term clinical results. © 2017 Wiley Periodicals, Inc.